Development of stimulus-driven attention test for unilateral spatial neglect – Accuracy, reliability, and validity. (16th February 2022) - Motomura, Kazuya; Amimoto, Kazu
Highlights: New assessment of stimulus-driven attention that responds to sudden targets. It detects unilateral spatial neglect that is not detected by conventional methods. The new assessment showed high accuracy and moderate reliability. It showed moderate correlation with the conventional assessments. Correlation with perceptual and cognitive items in daily life was higher. Abstract: We developed a simple method to assess stimulus-evoked attention function in unilateral spatial neglect (USN), and examined its accuracy, reliability, and validity. Thirty-one patients with USN and sixteen patients with right hemisphere damage without USN were given a task of reading Japanese characters that suddenly appeared on a display, and a reading or touching task of red Japanese characters that are arranged on the display. The sensitivity and specificity were calculated from the measurement results, and the cutoff value was calculated using the receiver operating characteristic curve. Area under the curve was used to evaluate the discriminatory ability. Reliability was calculated by the intraclass correlation coefficient using the test-retest method. Validity was assessed by correlating the scores of the new method with the scores of the traditional assessment, the behavioral inattention test, and the Catherine Bergego Scale. This new method was able to detect left USN with the same level of accuracy as the conventional assessment and showed moderate or better reliability. In addition, a moderate correlation was found with the conventional assessment, and a higher correlation was observed with items related to perception and cognition in daily life.